Model PjBL Berbantuan Media Tiktok untuk Membangun Kreativitas Belajar Peserta Didik Kelas VIII - Nur Asmarita; Thoha Firdaus; Effendi Effendi (Pendidikan Fisika Universitas Nurul Huda, 2023)
The purpose of this study was to determine the feasibility of the TikTok media-assisted PjBL model in building students' learning creativity in the substance pressure material in Class VIII MTs Nurul Huda Sukaraja. This type of research is research and development (R&D) with the Borg and Gall model design. The sources of this research are teachers, students, experts. Data collection was carried out using validation sheets, questionnaires, evaluations, and documentation. Data analysis in this research is using quantitative analysis techniques. Based on data analysis concluded; The PjBL model assisted by TikTok media in building student learning creativity is very feasible to use with the results of validating. The learning implementation plan of 90.00% and the learning creativity assessment rubric of 95.94%; the learning creativity of students in implementing the PjBL model assisted by TikTok media is very high or very creative with a percentage of 89.11%; Student responses to the application of the TikTok Media-assisted PjBL model in building student learning creativity were good or interesting with an average percentage of the questionnaire of 74.87%. Whereas the implementation of PjBL is said to be feasible and appropriate to be implemented in class VIII MTs